A study and evaluation of cutaneous adverse drug reaction in the patients attending dermatology department of tertiary care teaching hospital in Eastern Uttar Pradesh - Gupta, Dharmender; Gairola, Bikash; Kumar, Bijay; Bharath, Masuram; Ansari, Mohd Shadab (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Cutaneous adverse drug reactions (CADRs) are most frequently reported type of ADRs and can be caused by variety of drugs. The clinical patterns of adverse cutaneous drug reactions and the drug responsible for them is changing every year due to the emergence of newer molecules and changing trends in the use of drugs. Methods: This was a prospective, cross-sectional and observational study done for a period of 6 months to evaluate the clinical pattern of CADRs and their causative drugs in the tertiary health care. Results: Over all 55 patients were detected with cutaneous adverse drug reaction. The majority of CADRs were in the age group of 18-35 years (63.46%). Fixed drug eruptions (FDE) being the most common adverse cutaneous drug reaction (34.68%) followed by maculopapular rash (23%), NSAIDs being the most common, followed by antimicrobial agents. Conclusions: Knowledge of these drug eruptions, the causative drugs are essential for the clinicians and implementing the ADRs reporting and monitoring system, one can promote drug safety and better patients care, among health care professionals.